A Facile Self-assembly Synthesis of Hexagonal ZnO Nanosheet Films and Their Photoelectrochemical Properties - Zhang, Bin; Wang, Faze; Zhu, Changqing; Li, Qiang; Song, Jingnan; Zheng, Maojun; Ma, Li; Shen, Wenzhong (Nano-Micro Letters, 2015)
Here, large-scale and uniform hexagonal zinc oxide (ZnO) nanosheet films were deposited onto indium tin oxide (ITO)-coated transparent conducting glass substrates via a facile galvanic displacement deposition process. Compared with other commonly used solution methods, this process avoids high temperature and electric power as well as supporting agents to make it simple and cost-effective. The as-fabricated ZnO nanosheet films have uniform hexagonal wurtzite structure. The photoelectrochemical (PEC) cell based on ZnO nanosheet film/ITO photoelectrode was also fabricated and its performance was improved by optimizing the solution concentration. A higher photocurrent density of ~500 μA cm−2 under AM 1.5 G simulated illumination of 100 mW cm−2 with zero bias potential (vs. Ag/AgCl electrode) was obtained, which may ascribe to the increased surface-to-volume ratio of disordered ZnO nanosheet arrays. Our developed method may be used to deposit other oxide semiconductors, and the ZnO nanosheet film/ITO PEC cell can be used to design low-cost optoelectronic and photoelectrochemical devices.